Demographic, clinical and biochemical profile of patients with polycystic ovary syndrome: a study in a tertiary care hospital of Bangladesh - Bimol Kumar Agawala; Nausher Azimul Huq; Ratan Kumar Agarwala; Shahin Ibn Rahman; Shyamal Chandra Banik; Ranodhir Chakraborty (BIRDEM Medical Journal, 2024)
Background: Polycystic ovary syndrome (PCOS) is a common and heterogeneous endocrine disorder, marked by irregular or absent menstrual cycles, excess androgens and polycystic ovaries. The prevalence and diagnosis of PCOS vary depending on the clinical criteria employed, with a prevalence as high as 8-13% when using the Rotterdam criteria. This study was designed to assess the demographic, clinical and biochemical profile of patients with PCOS. Methods: This cross-sectional study was conducted in the Department of Obstetrics & Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2015 to December 2016. The study included 51 women aged 20-35 years with PCOS. Participants were selected using convenient sampling. Data was collected through a semi-structured questionnaire and analyzed using MS Office tools and SPSS Version 23.0. Results: The mean age and BMI of our participants were 25.0±32 years and 27.0±3.1 kg/m2 respectively. The most common symptom was oligomenorrhoea (74.5%) and the ultrasonographic finding was polycystic ovary (92%). The mean s. testosterone and D2 serum luteinizing hormone (LH) were 1.8±0.9 ng/ml and 12.7±6.7 mIU/mL respectively and s. LH/FSH ratio was increased in 30 (58.8%) patients. The mean fasting insulin, fasting blood glucose and HOMA IR were 27.3±10.7 ìU/ml, 5.1±0.8 mmol/L and 4.1±1.3 respectively. Regarding lipid profile status of study subject, 68.60 % had high LDL and 60.60% had high triglyceride level. Conclusion: The most common clinical feature was oligomenorrhoea and polycystic ovary in ultrasonography. LDL cholesterol and triglycerides were higher in comparison to total cholesterol in PCOS cases. BIRDEM Med J 2024; 14(2): 65-69